1999
DOI: 10.2307/177000
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Mutualism: Competition, Tree Morphology, and Pollen Production in Limber Pine Clusters

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. All aspects of a mutualism may not be optimal for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Only genetic analysis can distinguish between the morphologically similar multiple-trunk trees and tree clusters. Several studies have found that the proportion of single stems ranges from 65% to 80% over the elevation range covered by this study (Lanner and Vander Wall 1980;Schuster and Mitton 1991;Carsey and Tomback 1994;Feldman et al 1999). The composition of tree clumps is highly variable ranging from 18% (Schuster and Mitton 1991) to 81% (Carsey and Tomback 1994) composed of genetic individuals (tree clusters).…”
Section: Survey Methodsmentioning
confidence: 77%
“…Only genetic analysis can distinguish between the morphologically similar multiple-trunk trees and tree clusters. Several studies have found that the proportion of single stems ranges from 65% to 80% over the elevation range covered by this study (Lanner and Vander Wall 1980;Schuster and Mitton 1991;Carsey and Tomback 1994;Feldman et al 1999). The composition of tree clumps is highly variable ranging from 18% (Schuster and Mitton 1991) to 81% (Carsey and Tomback 1994) composed of genetic individuals (tree clusters).…”
Section: Survey Methodsmentioning
confidence: 77%
“…Seeds of pinyon pine (Pinus edulis) (Christensen et al 1991) and limber pine (Pinus jlexilis) (Feldman et al 1999) are primarily dispersed by the seed predator Clark's Nutcracker (Nucifraga columbiana). Nutcrackers ensure against winter forage scarcity by subterranean caching of cone seeds while cones are plentiful in the fall.…”
Section: Seed Deposition Into Favorable Microhabitatmentioning
confidence: 99%
“…Nutcrackers ensure against winter forage scarcity by subterranean caching of cone seeds while cones are plentiful in the fall. In a typical winter, about one-fifth of the cached seeds are not recovered (Feldman et al 1999). Some fruits such as European hawthorn (Crataegus monogyna), and holly (llex aquifolium), contain secondary compounds that are mildly toxic to many avian consumers.…”
Section: Seed Deposition Into Favorable Microhabitatmentioning
confidence: 99%
See 1 more Smart Citation
“…In transporting seeds to new environments, animal dispersers can influence plant performance by setting the stage for subsequent ecological interactions with competitors, predators, disease agents, and herbivores (e.g., Janzen 1970, Augspurger 1983, Kalisz et al 1999. Although dispersal to new locations can benefit plants in numerous ways, it is less widely recognized that these services may also impose a variety of costs (e.g., Feldman et al 1999). Understanding the net effect of dispersal, and thus its significance as an ecological and evolutionary force, will depend on the extent to which costs of dispersal outweigh the benefits.…”
Section: Introductionmentioning
confidence: 99%